Fighting poverty, hunger and malnutrition with neglected and underutilized species: needs, challenges and the way forward - Padulosi, S.; Bioversity International; Thompson, J.; Rudebjer, P.G. (Bioversity International, 2013)
Neglected and underutilized species (NUS) are those to which little attention is paid or which are entirely ignored by agricultural researchers, plant breeders and policymakers1. Typically, NUS are not traded as commodities. They are wild or semi-domesticated varieties and non-timber forest species adapted to particular, often quite local, environments. Many of these varieties and species, along with a wealth of traditional knowledge about their cultivation and use, are being lost at an alarming rate. Yet NUS present tremendous opportunities for fighting poverty, hunger and malnutrition. And they can help make agricultural production systems more resilient to climate change. Not least, acknowledgment of the value of NUS in traditional foods and cultures can empower indigenous communities (women in particular) and reaffirm their identity. The time for action on NUS is now. There is a growing realization that agriculture must diversify. NUS have an important role to play in advancing agricultural development beyond the Green Revolution model of improving and raising the yields of staple crops.